Differential metabolism of L–phenylalanine in the formation of aromatic volatiles in melon (Cucumis melo L.) fruit. (April 2018) - Gonda, Itay; Davidovich-Rikanati, Rachel; Bar, Einat; Lev, Shery; Jhirad, Pliaa; Meshulam, Yuval; Wissotsky, Guy; Portnoy, Vitaly; Burger, Joseph; Schaffer, Arthur A.; Tadmor, Yaakov; Giovannoni, James J.; et al.
Abstract: Studies on the active pathways and the genes involved in the biosynthesis of L-phenylalanine-derived volatiles in fleshy fruits are sparse. Melon fruit rinds converted stable-isotope labeled L-phe into more than 20 volatiles. Phenylpropanes, phenylpropenes and benzenoids are apparently produced via the well-known phenylpropanoid pathway involving phenylalanine ammonia lyase (PAL) and being ( E )-cinnamic acid a key intermediate. Phenethyl derivatives seemed to be derived from L-phe via a separate biosynthetic route not involving ( E )-cinnamic acid and PAL. To explore for a biosynthetic route to ( E )-cinnamaldehyde in melon rinds, soluble protein cell-free extracts were assayed with ( E )-cinnamic acid, CoA, ATP, NADPH and MgSO4, producing ( E )-cinnamaldehyde in vitro . In this context, we characterized CmCNL, a gene encoding for ( E )-cinnamic acid:coenzyme A ligase, inferred to be involved in the biosynthesis of ( E )-cinnamaldehyde. Additionally we describe CmBAMT, a SABATH gene family member encoding a benzoic acid: S -adenosyl-L-methionine carboxyl methyltransferase having a role in the accumulation of methyl benzoate. Our approach leads to a more comprehensive understanding of L-phe metabolism into aromatic volatiles in melon fruit. Graphical abstract: Highlights: L-phenylalnine is catabolized into 21 phenolic volatiles in melon ( C. melo ) fruit. Melons phenolic volatiles are produced via both PAL-dependent and PAL–independent pathways. C. melo cell-free extracts support ( E )-cinnamaldehyde formation from ( E )-cinnamic acid. C. melo ( E )-cinnamic acid:CoA ligase (CmCNL) supports cinnamoyl CoA production. C. melo benzoic acid O -methyltransferase (CmBAMT) supports methyl benzoate formation.